Modeling and finite element simulation of the bifunctional performance of a microporous structural battery electrolyte - Tu, Vinh (My University, 2019)
The structural battery composite is an innovative solution for a light-weight storage of electrical energy. It is multifunctional since it carries mechanical loads and stores electrical energy simultaneously. Such multifunctional materials will become important for e.g. the electrification of vehicles since large weight-reductions can be gained. This innovation will contribute greatly to realizing the vision of a carbon-neutral circular economy. Due to the infancy of this technology, the structural batteries still need to be developed further. The main purpose of the project is to model and simulate the diffusive transport of lithium ions through the structural battery electrolyte (SBE) between the structural battery electrodes in a laminar setup, and to simulate the SBE’s mechanical behaviour. The SBE is a microporous polymer matrix filled with a liquid electrolyte. By generating an artificial SBE microstructure and performing some virtual material testing, it will become possible to evaluate the effective multifunctional performance of the SBE for varying pore sizes. The artificial SBE microstructure is generated by manipulating the stationary heat equation. It is possible to choose heat sources and heat sinks in a clever fashion in order to obtain the desired shape for the artificial microstructure. The choice of heat sources and heat sinks is based on a periodic Voronoi tessellation that is embedded in a solid unit cube. By letting the Voronoi edges be heat sources, and the Voronoi seeds be heat sinks, an artificial microstructure which is microporous and bicontinuous is obtained after some modification and post-processing of the temperature field. The multifunctional performance of the SBE is evaluated by applying the theory of computational homogenization on the artificial SBE microstructure which serves as a statistical volume element with the ability to almost fully characterize the material’s heterogeneities. In particular, the weakly periodic boundary conditions are used. The results from the virtual material testing indicate that the lower bound of the stiffness increases for increasing volume fraction of polymer matrix, while the upper bound of the stiffness and the ionic conductivity decreases. Furthermore, the effective diffusivity seems to scale linearly with the volume fraction while the bounds of the effective stiffness seem to scale non-linearly. Although the goal of the project is to mimic the SBE in the structural battery, the end result is a quite general recipe on artificial microstructure generation. Nevertheless, this thesis paves the way for more rigorous artificial SBE microstructure generation in the future.
Keywords: Maskinteknik; Materialteknik; Produktion; Mechanical Engineering; Materials Engineering; Production